Implications on Educational Management During the COVID-19 Pandemic - Alfalasi, Khulood (2021)
Education sector faced a significant transition recently, shifting from face-to-face classes to online classes due to the unprecedented COVID-19 pandemic. The pandemic's consequences affected teaching and learning and negatively influenced students' psychological well-being. This study aimed to explore the pandemic's impact on undergraduate students' academic stress, especially as related to their academic performance. Furthermore, the students' coping strategies during the pandemic, if any, were investigated. The researcher used a mixed-method approach, and surveyed 191 participants from the College of Education (COE) and students from other colleges enrolled in elective courses in the COE in one selected university in the UAE. The qualitative data was collected through a focus group discussion with seven COE undergraduate students doing their internship. The key findings showed that the xenophobia factor (the fear of strangers) causes the highest stress levels, and students reported that workload and time constraint factors were top stressors. Also, A-range students (students with a GPA of 3.7 and above) were significantly less stressed than B-range students (GPA of 2.7–3.3). First-year students were significantly more stressed than second-year, third-year, and fourth-year students. It was found that internship students expressed their stress and anxiety due to the change to online education caused by the pandemic. Single site focus was a key limitation of the study and it was recommended to increase the number of sites and samples. In conclusion, this study helped educational leadership and psychologists to better understand students' needs and create innovative educational platforms.